2014
DOI: 10.1016/j.patrec.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised dense crowd detection by multiscale texture analysis

Abstract: This study introduces a totally unsupervised method for the detection and location of dense crowds in images without context-awareness. With the perspective of setting up fully autonomous video-surveillance systems, automatic detection and location of crowds is a crucial step that is going to point which areas of the image have to be analyzed. After retrieving multiscale texturerelated feature vectors from the image, a binary classification is conducted to determine which parts of the image belong to the crowd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Experiments with human operators showed that the system leads to a significant reduction of missed people by using the interactive functionality, especially for large time intervals [5]. The tracking system was integrated and validated in a crowded [13] [19] shopping mall in the Netherlands, in collaboration with five SMEs [4]. The system performed consistently and robustly.…”
Section: Graphical User Interfacementioning
confidence: 99%
“…Experiments with human operators showed that the system leads to a significant reduction of missed people by using the interactive functionality, especially for large time intervals [5]. The tracking system was integrated and validated in a crowded [13] [19] shopping mall in the Netherlands, in collaboration with five SMEs [4]. The system performed consistently and robustly.…”
Section: Graphical User Interfacementioning
confidence: 99%
“…Sample results are shown in Figure 14. Similarly, Fagette et al [136] proposed an unsupervised method using multi-scale texture-based features to detect and localize dense crowds in images. The unsupervised method allows detection on images without the need to have prior knowledge of the scene or context.…”
Section: Crowd Segmentationmentioning
confidence: 99%
“…Terrestrial cameras already provide the major part of this information as images and videos. In general, a lot of research has been done to process this huge amount of data automatically [1][2][3][4], and most often with the goal of crowd counting [5][6][7][8], person tracking [9,10], or behavior understanding [11,12]. However, all these methods are tested on benchmark datasets containing terrestrial images or videos, and do not consider aerial images for crowd counting.…”
Section: Background and Motivationmentioning
confidence: 99%